Impact of hydrogel spacer injections on interfraction prostate motion during prostate cancer radiotherapy. (2nd July 2016) - Picardi, Cristina; Rouzaud, Michel; Kountouri, Melpomeni; Lestrade, Laetitia; Vallée, Jean Paul; Caparrotti, Francesca; Dubouloz, Angèle; Miralbell, Raymond; Zilli, Thomas
Abstract: Background The dosimetric advantage of prostate-rectum spacers to displace the anterior rectal wall outside of the high-dose radiation regions has been clearly established in prostate cancer radiotherapy (RT). The aim of this study was to assess the impact of hydrogel spacer (HS) in the interfraction prostate motion in patients undergoing RT for prostate cancer. Material and methods Twenty prostate cancer patients implanted with three fiducial markers (FM) with ( n  = 10) or without ( n  = 10) HS were analyzed. Displacements between the prostate isocenter based on the FM's position and the bony anatomy were quantified in the left-right (LR), anterior-posterior (AP), superior-inferior (SI) axes by offline analyses of 122 cone beam computed tomography scans. Group systematic (M), systematic (Σ) and random (σ) setup errors were determined. Results In patients with or without HS, the overall mean interfraction prostate displacements were 0.4 versus −0.4 mm ( p  = 0.0001), 0.6 versus 0.6 mm ( p  = 0.85), and −0.6 mm versus −0.3 mm ( p  = 0.48) for the LR, AP, and SI axes, respectively. Prostate displacements >5 mm in the AP and SI directions were similar for both groups. No differences in M, Σ and σ setup errors were observed in the three axes between HS + or HS- patients. Conclusions HS implantation does not significantly influence the interfraction prostate motion in patients treated with RT for prostate cancer. The major expected benefit of HS is a reduction of the high-dose levels to the rectal wall without influence in prostate immobilization.